Farmgate Private Standards and Price Premium: Evidence From the GlobalGAP Scheme in Kenya's French Beans Marketing - Isaac Maina Kariuki; Jens-Peter Loy; Thomas Herzfeld (Agribusiness, 2012)
The proliferation of private quality and assurance schemes in international trade is defining market access in high value chains. The prime concern for small-scale producers is whether price premiums are realizable due to compliance. Using French beans marketing, the authors find that GlobalGAP certification, produce traceability, number of suppliers, competition for supplies, direct procurement, a good road network, and supply contracts have positive farmgate price effects for smallholders. Potential policy implications are drawn.
Keywords: L11; L23; 330